Admonition of The Clan in The Pre-Islamic Poem: مضامين قصيدة العتاب الجاهلية (Journal of Hama University, 2024)
The research strives to extrapolate the contents of the pre-Islamic admonition poem. In order to achieve its goal, it relies on the concept of the clan and its status in relation to the individual. It explains of admonition as an emotional concept and a poetic purpose. It proves the meanings of the clan's admonition in the pre-Islamic poem, and relate each meaning with the most important stylistic features and artistic phenomena that it contained.The importance of studying admonition comes from the status of the individual in the clan and the status of the clan in the hearts of its members in a tribal society whose laws do not allow deviating from the clan or the failure of the clan to support its members, or the failure of individuals to help it, whether it is wise or ignorant. It also does not allow the failure of the clan to support its members.The research relies on the descriptive analytical approach in order to achieve the goal it aims at. After extrapolating the contents of the Admonition in the pre-Islamic poem, it concluded that the Admonition is a poetic purpose and an emotional position, motivated by loyalty to the clan, in which the poets moved away from opposition to clan and avoided the meanings that arouse hatred and abandonment.
Keywords: - Admonition - Clan - Poem - Pre-Islamic - Belonging